Effectiveness of public health messaging and communication channels during smoke events: A rapid systematic review. (15th May 2017) - Fish, Jennifer A.; Peters, Micah D.J.; Ramsey, Imogen; Sharplin, Greg; Corsini, Nadia; Eckert, Marion
Abstract: Exposure to smoke emitted from wildfire and planned burns (i.e., smoke events) has been associated with numerous negative health outcomes, including respiratory symptoms and conditions. This rapid review investigates recent evidence (post-2009) regarding the effectiveness of public health messaging during smoke events. The objectives were to determine the effectiveness of various communication channels used and public health messages disseminated during smoke events, for general and at-risk populations. A search of 12 databases and grey literature yielded 1775 unique articles, of which 10 were included in this review. Principal results were: 1) Smoke-related public health messages are communicated via a variety of channels, but limited evidence is available regarding their effectiveness for the general public or at-risk groups. 2) Messages that use simple language are more commonly recalled, understood, and complied with. Compliance differs according to socio-demographic characteristics. 3) At-risk groups may be advised to stay indoors before the general population, in order to protect the most vulnerable people in a community. The research included in this review was observational and predominantly descriptive, and is therefore unable to sufficiently answer questions regarding effectiveness. Experimental research, as well as evaluations, are required to examine the effectiveness of modern communication channels, channels to reach at-risk groups, and the 'stay indoors' message. Highlights: Messages are conveyed via various channels, however, limited evidence is available regarding effectiveness of channels. Multiple modes of communication, including bidirectional means, may be useful for reaching a wide audience. Social media platforms are popular communication channels and early evidence suggests they may be useful during smoke events. Messages that use simple language are more commonly recalled, understood, and complied with. Evaluations and experimental research are required to examine the effectiveness of communication channels and messages.